PERAN APLIKASI SISTEM PENGELOLAAN PENGADUAN PELAYANAN PUBLIK NASIONAL – LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT SEBAGAI MEDIA PENGADUAN PELAYANAN PUBLIK DI KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study aims to analyze the role of the SP4N Lapor application as a complaint handling platform in improving the quality of public services in Gowa Regency. This study applies a qualitative approach using a case study method, where data is obtained through in-depth interviews with relevant parties, field observations, report analysis, and documentation collection. The results show that SP4N Lapor plays a significant role in strengthening public participation, accelerating government agency responses to complaints, and increasing accountability and transparency in public services. However, there are still obstacles such as a lack of application socialization at the community level, and there are still several complaints that have not been followed up by several agencies due to budget constraints. These findings imply that they can contribute to understanding the needs and expectations of the community in using the complaint platform. It is hoped that public participation in reporting complaints will increase, thereby creating a more accountable and responsive environment.